Updated list of the mammals of Costa Rica, with notes on recent taxonomic changes - Mora, José Manuel; Ruedas, Luis A. (Zootaxa, 2023)
Although Costa Rica occupies a mere 0.03% of the Earth’s land area, it nevertheless has recorded within its borders approximately 5% of the global diversity of mammals, thus making it one of the world’s megadiverse countries. Over the past ten years, 22 species have been added to the country’s inventory, bringing the total number known as here documented to 271; Chiroptera account for ten of these, having grown to 124 from 114; rodents have increased by eight species, from 47 to 55, with the caveat that we include three invasive species of Muridae that have gone feral. In contrast, the number of orders has decreased by one, by Artiodactyla incorporating the former Cetacea. Notes are provided for all taxonomic novelties since the last update. Since the first taxonomic compendium of the mammals of Costa Rica in 1869, the number of known species has grown by approximately 1.22 species year-1 (R2 = 0.96). Since 1983 however, this growth rate has been 1.64 species year-1 (R2 = 0.98). Despite this strong growth, an asymptote in the number of known species has not been reached. Conservation remains a primary need: over 60% of the country’s mammal species show population trends that are decreasing (13%), unknown (37%), or not assessed (11%), based on IUCN criteria. These analyses suggest that much remains to be known regarding the number of mammal species living in Costa Rica, but also that much more remains to be done to safeguard Costa Rica’s exceptional biodiversity heritage.